Utilization of shallot extract and administration of indole acetic acid to Chrysanthemum sp in vitro culture - DAFNI MAWAR TARIGAN; WAN ARFIANI BARUS; FEMIL YANDA HAKIM NASUTION; ANGGRIA LESTAMI (Jurnal Natural, 2022)
Chrysanthemum sp is a plant that has the potential to be developed in Indonesia, apart from being an ornamental flower, it can also be used as a herbal medicine. One of the efforts to develop chrysanthemum can be done in vitro by using organic growth regulators such as shallot extract and indole acetic acid (IAA). The research aims to identify the effect of shallot extract and IAA on the growth of Chrysanthemum sp. The research was conducted at UPT Central Horticulture Seed Center, Medan Johor, in December 2019 - January 2020. The research used a factorial Completely Randomized Design (CRD) with 2 factors, namely the first factor was shallot extract which consisted of 4 levels, namely 0, 35, 70, and 105 g/L water. The second factor was IAA which consisted of 4 levels, namely 0.6, 0.9, 1.2, and 1.5 mg/L water. The results showed that the administration of shallot extract had no significant effect on the growth of chrysanthemum, but the administration of IAA had a significant effect on the number of leaves and plant height with the best concentration at 0.6 mg/L water. The interaction of the two treatments also had no significant effect on the growth of chrysanthemum.